1998
DOI: 10.1021/np970467w
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Cytotoxic Evaluation of Marine Sponge-Derived Norterpene Peroxides

Abstract: The marine sponge Diacarnus cf. spinopoculum has provided a series of norterpenes, including five new compounds (7-11), two new ent-compounds [(-)-1a and (+)-1b], and three known compounds (2a, 2b, and 12). Eight of these compounds represent additional examples of the muqubilin/sigmosceptrellin classes (norsesterterpene peroxides) or the nuapapuin class (norditerpene peroxides). Also isolated were dinorditerpenones 11 and 12, which are biosynthetically related to the muqubilin/sigmosceptrellin structure classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
130
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(135 citation statements)
references
References 19 publications
5
130
0
Order By: Relevance
“…Comparison of the NMR spectra of 2 (Tables 1 and 2) with those of 1 revealed that 2 possesses a similar structure, except for the absence of the resonances for the C-1 methyl ester observed in 1. The downfield shift in the 13 C resonance observed for C-1 in 2 (δ = 180.1 ppm), relative to the δ = 174.2 ppm observed for C-1 in 1, was consistent with a proposed structure that contains a C-1 carboxylic acid. The HRESIMS mass spectrum of 2 displayed a molecular ion that was 14 mass units less than that observed for 1.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Comparison of the NMR spectra of 2 (Tables 1 and 2) with those of 1 revealed that 2 possesses a similar structure, except for the absence of the resonances for the C-1 methyl ester observed in 1. The downfield shift in the 13 C resonance observed for C-1 in 2 (δ = 180.1 ppm), relative to the δ = 174.2 ppm observed for C-1 in 1, was consistent with a proposed structure that contains a C-1 carboxylic acid. The HRESIMS mass spectrum of 2 displayed a molecular ion that was 14 mass units less than that observed for 1.…”
Section: Resultssupporting
confidence: 79%
“…The 1 H, 13 C and 13 C DEPT NMR spectra of 3 (Tables 1, 2) were closely related to those of 1. The 13 C NMR spectrum of 3 (Table 2) exhibited seven methyl, ten methylene, three methine, and five quaternary carbon resonances.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…1) Sponges of genus Diacarnus are recognized as being prolific sources to produce terpene peroxides and related derivatives, which include norterpene ketones, dienes, diols and other types of compounds. [2][3][4][5][6][7][8] From a biosynthetic perspective, the biosynthetic origin of some or all marine norterpene cyclic peroxides involved a common intermediate C6 hydroperoxide, undergoing a "Michael addition" to an adjacent α,β-unsaturated carboxylic acid or ester moiety. 6) As an offshoot of the biosynthetic pathway, the norterpene ketones can be derived from the hydroperoxide carboxylic aid precursor by oxidative degradation.…”
Section: New Metabolites From the South China Sea Sponge Diacarnus Mementioning
confidence: 99%
“…6) Such ketones are increasingly being identified as minor co-metabolites with norterpene cyclic peroxides. 3,[9][10][11] Recently, attention has been drawn on these metabolites because of their pharmaceutical properties, including antimalarial, 8,12) antimicrobial, 12) Trypanosoma brucei inhibitory, 13) sea urchin egg cell-division inhibitory, 14) cytotoxic, 4,7,15) antiulcer and antihypotensive activities. 16) As our previous chemical research on the sponge D. megaspinorhabdosa, five norterpene cyclic peroxides diacarperoxides H-L have been isolated.…”
Section: New Metabolites From the South China Sea Sponge Diacarnus Mementioning
confidence: 99%